PERANCANGAN SISTEM APLIKASI LAUNDRY PADA CILOULA LAUNDRY CIRACAS BERBASIS JAVA NETBEANS - Agnes Novri Yanti; Ahmad Fauzi; Andi Dwi Pangestu (CV. Denasya Smart Publisher, 2024)
Into the modern era, the country information technology has grown faster and sophisticated. Development follow with the technology also in the the use of computers and internet among the, demanding almost all aspects life can be adjusting to circumstances.Based on reports of cooperation between we are social with hootsuite from january 2021 mobile phone users globally reached 5,22 billion and by internet users 4,66 billion. the purpose in this research is to develop the application system of data collection in them in order to laundry business in computerized , as well as to reduce its use of paper , recording the data and store data in a database .So that employees faster in data processing laundry .Research methods that were used observation is the method where is the writer observe live how a system of walking that is added to its ciloula laundry .Next writer understand the system running in order to obtain conclusion of the problem that aims to design the system next .